Examining COVID-19 vaccination coverage and acceptability among migrants in transit through Mexico during 2021–2022: Insights from shelter surveys and interviews - René Leyva-Flores; Belkis Aracena-Genao; Christine Allen; Diana Gómez-López; Ietza Bojórquez-Chapela; Ricardo Cortés-Alcalá (PLoS ONE, 2025)
Mexico faced significant obstacles in achieving COVID-19 vaccination coverage for migrants, particularly irregular migrants, asylum seekers, and refugees. In other contexts, migrant vaccination coverage has been influenced by prioritization policies, identification requirements, and various sociodemographic, migratory, and health factors, though these had not been fully explored in Mexico. This study analyzed factors associated with COVID-19 vaccine coverage among migrants in transit through Mexico. From November 2021 to May 2022, a convenience sample of 2,355 migrants across six shelters was surveyed on vaccination history and acceptance, as well as sociodemographic, migration, and health characteristics. To complement the survey, semi-structured interviews with migrants and key informants explored access barriers and attitudes toward COVID-19 vaccination. Of respondents, 61.1% reported receiving at least one COVID-19 vaccine dose, with 67.6% vaccinated prior to arriving in Mexico. Factors associated with vaccination included education level, country of prior residence, history of COVID-19 infection (OR = [95% CI, 1.081–1.737]), and COVID-19 testing history (OR = [95% CI, 3.825–5.999]). Among unvaccinated respondents, 81.4% expressed willingness to vaccinate, often viewing it as “protection against complications or death” and a “requirement for movement between countries.” Among respondents, 7.2% expressed concerns related to misinformation. Findings suggest that while many migrants were vaccinated before arrival, inconsistent ID requirements and age-based restrictions impeded coverage within Mexico. Addressing misinformation and aligning local practices with national policies could improve vaccine access for this population.